A p53/miR-30a/ZEB2 axis controls triple negative breast cancer aggressiveness. Issue 12 (December 2018) - di Gennaro, Alessandra; Damiano, Valentina; Brisotto, Giulia; Armellin, Michela; Perin, Tiziana; Zucchetto, Antonella; Guardascione, Michela; Spaink, Herman; Doglioni, Claudio; Snaar-Jagalska, B.; Santarosa, Manuela; Maestro, Roberta
Abstract Inactivation of p53 contributes significantly to the dismal prognosis of breast tumors, most notably triple-negative breast cancers (TNBCs). How the relief from p53 tumor suppressive functions results in tumor cell aggressive behavior is only partially elucidated. In an attempt to shed light on the implication of microRNAs in this context, we discovered a new signaling axis involving p53, miR-30a and ZEB2. By an in silico approach we identified miR-30a as a putative p53 target and observed that in breast tumors reduced miR-30a expression correlated with p53 inactivation, lymph node positivity and poor prognosis. We demonstrate that p53 binds theMIR30A promoter and induces the transcription of both miRNA strands 5p and 3p. Both miR-30a-5p and -3p showed the capacity of targeting ZEB2, a transcription factor involved in epithelial–mesenchymal transition (EMT), tumor cell migration and drug resistance. Intriguingly, we found that p53 does restrain ZEB2 expression via miR-30a. Finally, we provide evidence that the new p53/miR-30a/ZEB2 axis controls tumor cell invasion and distal spreading and impinges upon miR-200c expression. Overall, this study highlights the existence of a novel axis linking p53 to EMT via miR-30a, and adds support to the notion that miRNAs represent key elements of the complex network whereby p53 inactivation affects TNBC clinical behavior.